Líquenes palpables (2017)
This project tackles how the designer connects with nature through tactile experience, in order to depict the way human-nature bond is built, into a design object. For the natural component, liches were studied both as inspiration and the factor that triggers the tactile approach to nature. This was examined under three conditions: the physical contact, the emotional contact and the intellectual contact. Each of these represents a stage observed in the way the designer approaches lichens and nature. Therefore, these are applied to the resulting textile surface taking into account the tactile aesthetics.--Tomado del Formato de Documento de Grado.